Comparison of the Effectiveness of Productive Waqf Management in Indonesia and Singapore: A Comparative Study - Mustofa, Imam; Hidayat, Irman; Royhan Alhak, Maftuh; Yuliana, Mia (Risalah Iqtishadiyah, 2024)
Waqf, as an instrument of Islamic philanthropy, has great potential in developing a sharia-based economy. In the Indonesian context, waqf can be used as a source of Muslim funds that can assist in managing waqf assets. Even though Indonesia has the largest Muslim population in the world, waqf management in Indonesia is still low. Singapore, as a country with a Muslim minority, has demonstrated the ability to utilize waqf funds optimally and productively. This research compares the regulation and management of waqf in Indonesia and Singapore with the aim of improving waqf management in Indonesia. The results of this research show that waqf regulations in Indonesia are contained in Law Number 41 of 2004 and Government Regulation Number 42 of 2006, while in Singapore they are contained in the Administration of Muslim Law Act (AMLA) Number 27 of 1966. In the development of productive waqf in Singapore, the istibdal method is used to increase the value and productivity of waqf assets. The Management of waqf in Singapore entrusted to the Islamic Assembly of Singapore (MUIS) and WAREES Investment Pte Ltd (Waqaf Real Estate Singapore) to manage endowment funds in Singapore. Management in the development of productive waqf in Singapore uses the istibdal method which is applied in various forms. Therefore, the role of regulations in implementing waqf management must have an impact on the development of waqf in a country, so that waqf becomes one of the instruments of Islamic philanthropy that can be used as a source of funds for Muslims who are able to encourage the economic progress of a country and improve the welfare of society.